Refractive index sensitivity of fibre optic long period gratings with SiO2 nanoparticle based mesoporous coatings - Korposh, Sergiy; Lee, Seung-Woo; James, Stephen W.; Tatam, Ralph P. (Cranfield University, 2011)
A fibre optic long period grating (LPG) with an nano-assembled mesoporous coating of alternate layers of poly (allylamine hydrochloride) (PAH) and SiO2 nanospheres was used for the development of a fibre-optic refractometer. PAH/ SiO2 films of different thickness have been deposited onto an LPG in order to study the effect of the film thickness on sensor performance. The device showed a sensitivity of 1927 nm/RIU over a RI range of 1.3233-1.4906.
Keywords: Fibre-optic sensor; Long period grating; Nanoporous film; refractive index; Refractometer